Development of a low cost smart meter to collecting data and in-place tests - Amaral, Haroldo L. M. do [UNESP]; Souza, Andre N. de [UNESP]; IEEE (Ieee, 2014)
The development of society, technology and changes in consumer behavior has led to changes in the techniques and technologies used for measuring electricity. Currently there are many studies concerning the benefit related to the use of smart meters. Besides its use for billing, the smart meters can be used to collect data from the power grid, allowing continuous monitoring. In market there are many electronic meters available in addition to development kits, however, depending on the application might become limited or inflexible about modifications in their characteristics. This paper presents the development of a smart meter with flexible structure and which can be suitable for different situations. One of the main goals was to develop a smart meter that combines precision and capacity to store collected data for further analysis. This goal was achieved and the equipment developed proved to be a very efficient tool for monitoring the network, their magnitudes and also the behavior of consumers.